Village SDGs and Social Mapping: Efforts to Recognize the Potential of Village Towards Achieving the SDGs - Yulianto; Inayah, Astiwi; Fahmi, Teuku; Hidayati, Dewi Ayu; Meilinda, Selvi Diana (Talenta Publisher, 2023)
The article focuses on efforts to describe social mapping in recognizing the potential of Kiluan Negeri Village in supporting the achievement of village Sustainable Development Goals (SDGs). This qualitative study uses several data collection techniques, including interviews, focus group discussions, and unstructured observation. The results of the study show that in the environmental aspect, there is no integrated environmental management mechanism in Kiluan Negeri Village; in the social aspect, Kiluan Negeri Village has a good enough social capital to start optimizing the potential of the village they have; and in the economic aspect, the Kiluan Negeri Village holds great potential in the field of the tourism economy. For this reason, it is necessary to establish partnerships (government, private sector, academia, media) and explore collaboration with other villages.